An overview of analgesic methodologies in orthodontics - Alqahtani, Jamal M.; Alzaid, Sarah A.; Aldhaban, Omar A.; Alshdokhe, Elaf D.; Alhellal, Saleh A.; Alotaibi, Yazeed R.; Alyami, Hassan A.; Albalawi, Salman S.; Alharthi, Hassan M.; Hakami, Maram M.; Alblowi, Atheer A. (International Journal Of Community Medicine And Public Health, 2023)
Orthodontic treatments aim to enhance teeth functionality and aesthetics through various methods like permanent, removable, and functional appliances. These interventions may involve teeth removal, surgical procedures for alignment, and even jaw position adjustments. The treatment typically starts with the placement of an orthodontic device, followed by periodic adjustments. One major concern for patients is the associated pain, directly linked to the applied force. Various devices influence pain intensity, with fixed devices being more painful. Pain peaks after certain adjustments, like placing separators, and is attributed to decreased blood flow due to brace-induced force. Pain is the primary reason some patients consider discontinuing treatment. Pain management involves both pharmacological and non-pharmacological approaches, including the promising but still under-researched low-level laser therapy (LLLT) and light emitting diodes (LEDs). Dietary changes also play a role during treatment due to pain. Proper nutrition and oral hygiene guidance are essential from orthodontists and general dentists.